2000
DOI: 10.1021/jp001135u
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and Photophysical Properties of Fac-Re(I) Tricarbonyl Complexes:  A Comparison of Monomer and Polymer Species with −ReI(CO)3Phen Chromophores

Abstract: The photochemical and photophysical properties of a polymer containing nearly 200 pendant groups Re(CO)3(1,10-phenanthroline)+ bonded to poly-(vynilpyridine)600 and the related monomer pyRe(CO)3(1,10-phenanthroline)+ were investigated in solution phase. The yield of formation and the kinetics of decay of the MLCT excited state were found to be dependent on medium and laser power. MLCT excited states in the polymer undergo a more efficient annihilation and/or secondary photolysis than in the monomer. In the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 14 publications
2
61
0
7
Order By: Relevance
“…Terms & Conditions of access and use can be found at http://www.tandfonline.com/page/terms-and-conditions INTRODUCTION Numerous studies have been concerned with thermal and photochemical reactions of inorganic polymers in solid-and solution-phase. Some interest in their photochemical and photophysical properties is driven by their potential technical applications to catalysis and optical devices [1][2][3][4][5][6][7]. Previous work has shown marked differences between the photochemical and photophysical properties of the monomer pyRe(COh(1,10-(Phen) phenanthroline)+ and a related polymer (A}, with nearly 200 pendant groups -Re(CO)J(l, 10-phen)+ bonded to vpy (vinylpyridine} 600 , [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Terms & Conditions of access and use can be found at http://www.tandfonline.com/page/terms-and-conditions INTRODUCTION Numerous studies have been concerned with thermal and photochemical reactions of inorganic polymers in solid-and solution-phase. Some interest in their photochemical and photophysical properties is driven by their potential technical applications to catalysis and optical devices [1][2][3][4][5][6][7]. Previous work has shown marked differences between the photochemical and photophysical properties of the monomer pyRe(COh(1,10-(Phen) phenanthroline)+ and a related polymer (A}, with nearly 200 pendant groups -Re(CO)J(l, 10-phen)+ bonded to vpy (vinylpyridine} 600 , [2].…”
mentioning
confidence: 99%
“…The reductive quenching of the {(vpyh-vpyRe(COhphen+hoo excited states by TEOA is represented in Eq. (1) where the MLCT excited state is identified as -*Re(COh(l,lO-phen)+. Radicals (CH 2 0HCH 2 )N-cH·cH 2 0H are formed when TEOA is oxidized by TEOA •+ in Eq.…”
mentioning
confidence: 99%
“…If solutions of the polymer-free complexes were used instead of the polymer-grafted ones, the creation of similar conditions requires orders of magnitude larger concentrations of the complexes and/or light intensities. In addition to producing the simultaneous creation of two neighboring electronically excited pendent complexes by absorption of light, the experimental evidence has shown that migration of energy is possible, for example via a Forster energy transfer mechanism, from one electronically excited pendent complex to another in the ground state [31,32,42,43]. This energy hopping through the bundle has been observed in the photochemical processes of a number of polymers with grafted coordination complexes such as poly(HOAl III tspc) [31].…”
Section: Morphological Considerationsmentioning
confidence: 98%
“…Interest in the properties that L S imposes on the ÀRe I L A (CO) 3 moiety is brought about by possible applications of the Re complexes to biochemical processes [8 ± 11] and to CO 2 reduction [12]. Also, the derivatization of polymers with chromophores, e.g., with pendant ÀRe I L A (CO) 3 groups [13] has prompted investigation of the role of L S in the reactivity of some Re I monomers [14]. Literature reports show, for example, that the function of L S is to exert small perturbations that alter the electronic structure of the chromophore and modify its photophysics [6].…”
Section: ] àmentioning
confidence: 99%
“…IL 3 [Re I (aq-2-CO 2 )(2,2'-bipy)(CO) 3 ] hn'''; t 1 41 ns (12) MLCT bipy2Re 3 [Re I (aq-2-CO 2 )(2,2'-bipy)(CO) 3 ] hn'''; t 2 460 ns (13) [Re I ( T aq-2-CO ' spectrum calculated by extrapolation to the beginning of the laser flash is a convolution of two spectra (Fig. 6).…”
Section: A Potential Modulation Betweenmentioning
confidence: 99%